PENINGKATAN LITERASI TENTANG KESEHATAN MENTAL PADA SANTRI DI PONDOK PESANTREN DARUL ULUM II - Hasan, Hadri; Rahmy, Hafifatul Auliya; Nurkhayati, Ayu; Junaedah, Junaedah; Kurnia, Yuli; Amirullah, Muhammad; Arpan, Ahmad (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Mental health is an essential aspect of the definition of health presented by the World Health Organization. However, it has not received much attention even though the prevalence of mental disorders based on data from the 2023 Indonesian Health Survey shows that 1.4% experience depression, 4% experience symptoms of schizophrenia, and 2% experience mental health problems. Adolescents, including Islamic boarding school students, are one of the vulnerable groups experiencing mental health disorders. For this reason, lecturers and students of the Islamic Counseling Guidance Program carry out community service, which aims to provide students with knowledge about mental health. The method for implementing the activity was a lecture using slide share media and leaflets, which 56 students attended. The material presented is about the importance of mental health for Santri students, which includes definitions, characteristics of healthy mental health, examples of mental health disorders, and efforts to maintain mental health. Evaluation of activities using a five-question questionnaire and the results of the counseling can increase students' literacy regarding mental health. This service activity went well and received a good response from the Islamic boarding school management and students as participants in the outreach activity.